PENINGKATAN HASIL BELAJAR MATEMATIKA DI KELAS XI SEKOLAH MENENGAH KEJURUAN MENGGUNAKAN MODEL DISCOVERY LEARNING - Astri Silviana Jiwanti Mira; Yuliana Ina Tamu Nuhamara; Stevvileny Angu Bima; Elsy Senides Hana Taunu; Iona Lisa Ndakularak (Prima Magistra: Jurnal Ilmiah Kependidikan, 2024)
The selection of the right learning model is very influential on student learning outcomes. In its application at SMK negeri 5 Waingapu, it tends to still use the lecture method or conventional learning so that student learning outcomes are relatively low. Therefore, research was conducted by applying the Discovery Learning model. This study aims to determine the effectiveness of the Discovery Learning model in improving the mathematics learning outcomes of class XI students of SMK Negeri 5 Waingapu on matrix material. This research is a Classroom Action Research (PTK) whose implementation is carried out in two cycles with cycle 1 occurring two meetings and cycle 2 also two meetings with each cycle consisting of planning, action implementation, observation, and reflection. The subjects of this study were students of class XI TAV (Audio & Video Engineering) SMK Negeri 5 Waingapu which amounted to 17 people. This research is a Classroom Action Research (PTK) whose implementation was carried out in two cycles with cycle 1 occurring two meetings and cycle 2 also two meetings with each cycle consisting of planning, action implementation, observation, and reflection. The subjects of this study were students of class XI TAV (Audio & Video Engineering) SMK Negeri 5 Waingapu, totaling 17 people. The method of data collection is through tests (pretest and posttest questions) and documentation.  Which will be analyzed using qualitative descriptions consisting of data reduction stages, data presentation and data verification. Before being subjected to action, student learning outcomes were only 41.1% (7 students) who met the KKM and in cycle I students who met the KKM increased to 58.8% (10 students), also in cycle II students who met the KKM increased to 88.2% (15 students). So it can be concluded that the results of the study state that the application of the Discovery Learning model can improve students' mathematics learning outcomes on matrix material.